The Correlation between Language Skill and the Brain in the Second Verse of Surah Yusuf l ‘Alaqah al-Maharah al-Lughawiyyah wa al-‘Aql fi Surah Yusuf al-Ayah al-Tsaniyyah - Firdaus, Mohamad Anang; Ramadhan, Muhammad Rizki Syahrul; Amrulloh, Abdul Karim (Universitas Islam Negeri Raden Intan Lampung, 2023)
Arabic language had linguistic skills in its application. The Second Ayah (verse) of Surah Yusuf informed that there was a correlation between language skill and the brain. In terms of semantics, the choice of pronunciation and word in Al-Qur’an was based on the reason and the wisdom behind it. This article is necessary for language learning research by using neurology as a new approach in language skills learning. This article aimed to analyze and reveal a correlation and an appropriateness between the language skills in the Arabic language and the process of the human mind as mentioned in Surah Yusuf, the second verse. The data and evidence were obtained from books related to the subject of the research, a dialogical analysis between three scientific disciplines, such as commentary books, Arabic learning and neurology, with the method of content analysis of Al-Quran. The results of this research showed that the appropriateness of language skills in the Arabic language and the process of the human mind based on Surah Yusuf at the second verse were achieved. This result was reached based on three aspects, and it is from the opinions of scholars, interpreters, linguistics, and neurology. On the other hand, it was confirmed through this scientific research that there is no contradiction between the correct transmission and the frank reason. This article confirmed that the learning theory about maharah lughawiyah has the correlation with the workings of the human brain, according to what was stated in Surah Yusuf at the second verse.